Mergers and Acquisitions During the Covid-19 Pandemic in Poland - Tuzimek, Rafał (Journal of Finance and Financial Law, 2023)
The purpose of the article. The purpose of the study is to assess the impact of the COVID-19 pandemic on Polish companies’ M&A transaction activity, both occurring on the buy-side and seeking investors. Methodology. The survey was conducted by questionnaire on a sample of 111 companies operating in the industrial sector, and the results were compared with the number of transactions concluded in 2017–2022. Results of the research. The impact of the COVID-19 pandemic was felt by the majority of surveyed entities, but the magnitude of the impact differed significantly between potential buyers and sellers, who declared a greater negative impact of the pandemic on operations. The intention to sell the business was motivated by the impact of the COVID-19 pandemic outbreak in only 22% of cases. Companies with an active acquisition policy in most cases assessed their financial situation as stable, while the company’s financial problems were cited as one of the motives for the contemplated sale in about 20% of cases. It is noteworthy that for many companies the outbreak of the pandemic did not cause a change in the previously adopted strategy, which was maintained by 54% of companies planning acquisitions and 35% of companies seeking an investor. The outbreak of the pandemic caused a significant number of those considering buying a company to expect aľdrop in valuations and the emergence of investment opportunities. This phenomenon was not observed among sellers, which could indicate the periodic occurrence of a difference in price expectations between the parties to the transaction. An analysis of the number of ex-post transactions allows us to conclude that the risks identified in the initial phase of the pandemic did not negatively affect the M&A market in Poland, and after an initial slowdown due to lockdown and economic uncertainty, the Polish M&A market has returned to the upward trends observed before the outbreak of the COVID-19 pandemic.